Remorse Bias - Hanan, M. Eve (2018)
In this article, Professor M. Eve Hanan addresses how implicit cognitive biases may affect judges when they decide whether to credit defendants' displays of remorse and how we can lessen the effects of that bias. Part I of this article introduces the main ideas to be discussed. Part II establishes the salience of remorse to punishment decisions and then demonstrates the ambiguity involved in assessing the sincerity of remorse. Part III examines existing research on implicit biases associating African Americans with criminality to consider whether judges are likely to view African American defendants' expressions of remorse as insincere and, thus, unworthy of leniency. Part IV critiques and rejects two strategies for addressing implicit bias in punishment decisions - cabining discretion and sanitizing racial content from consideration. Part V offers recommendations to reduce the impact of racial bias on remorse assessments in punishment decisions